Prevalence of misconceptions that the Indian population possesses with regard to dental treatment- A survey - Kasabwala, Harsh; Nallaswamy, Deepak; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2019)
The utilisation of dental services is usually hampered due to multiple barriers. Some of them are, factors which are culturally influenced, misconceptions regarding oral health care, low education and poor health literacy level among the population. The main purpose of this study was to highlight the ritual and cultural practices that the population in India follows and their subsequent effect on the oral cavity. The present study was conducted all over India. The population were randomly selected. An online questionnaire was prepared. The questionnaire was related to the knowledge and beliefs of the population towards dental treatment. A total of 18 close ended question a were included. The survey proforma was sent to 300 individuals of different age groups across all the states in India, out of which 234 individuals responded. There was a general lack of knowledge among the population about the importance of dental treatment and the misbelieves they had regarding the same. The reason for this could be due to low education levels, low levels of awareness of oral hygiene practices and low socioeconomic status among certain population. Routine camps should be conducted where clinicians demonstrate oral hygiene practices and make the population aware regarding the importance of dental treatment.